BEBAN KERJA DAN PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Hamidah Nayati Utami; Tri Wulida Afrianty; Rahma Wulan Sari (Jurnal Bisnis Terapan, 2019)
This study aims to analyze the effect of workload on organizational commitment withwork stress as an intervening variable. A quantitative approach was undertaken forthis research. This research was conducted at PT. INDOLAKTO Purwosari with a total sample of 88 employees. Data collection was carried out using a survey questionnaire. The hypotheses in this study were tested by path analysis using SPSS version 25. The results of hypothesis testing showed that workload has a positive and significant effect on organizational commitment, Workload has a positive and significant effect on Job Stress, Job Stress has a positive and significant effect on organizational commitment, and job stress mediates the relationship between workload and organizational commitment.